(3hVY GdbhGYO (B:s 25 (3bGYOI ddBHGA hGdCegGJ (B/s - (3HjJQR, QhK s ((3GdQjGV (B:s (3ecJHI LQjQ,s, 2004)
(3jJfGhd GdcJGH (B25 (3bGYOI NGdUI hLGOI dJYde CWaGdc Gdbje hGdGfVHGW GdJGe(B.s
Keywords: (3JQHjI GdCWaGds; (3GdBHGA hGdCHfGAs -- (3YdGbGJ CSQjIs